Investigation of Flavonoid Extractives and their Contribution to Color of Dalbergia latifolia Roxb Wood - Masendra Masendra; Brandon Aristo Verick Purba; Denny Irawati; Ganis Lukmandaru (Masyarakat Peneliti Kayu Indonesia, 2021)
Dalbergia latifolia wood is a beautiful wood with color of dark purple to dark brown and rich in flavonoid compounds. This study aimed to investigate the presence of flavonoid compounds from D. latifolia wood and their contribution to its color. The D. latifolia wood sample was powdered and extracted with ethanol-toluene (1/2, v/v). The ethanol- toluene extract then was column chromatographed to obtain fraction 1 to fraction 12. Methylation was conducted to each fraction to detect flavonoid compounds by GC-MS. The results of GC-MS analysis showed that ethanol- toluene extract gave Fr- 1- Fr. 3 as soluble flavonoids (34.2%) and Fr. 4- Fr. 12 as insoluble polymers (62.6%). Furthermore, 12 flavonoids i.e latifolin, dalbergiphenol, chalcone, dalbergin, and their derivatives were characterised and these compounds might be significance in contributing to color of D. latifolia wood.